Listeria monocytogenes Growth Kinetics in Milkshakes Made from Naturally and Artificially Contaminated Ice Cream - Salazar, Joelle K.; Bathija, Vriddi M.; Carstens, Christina K.; Narula, Sartaj S.; Shazer, Arlette; Stewart, Diana; Tortorello, Mary Lou (Frontiers in Microbiology, 2018)
This study assessed the growth of L. monocytogenes in milkshakes made using the process-contaminated ice cream associated with a listeriosis outbreak in comparison to milkshakes made with artificially-contaminated ice cream. For all temperatures, growth kinetics including growth rates, lag phases, maximum populations, and population increases were determined for the naturally- and artificially-derived contaminants at 5, 10, 15, and 25°C storage for 144 h. The artificially-inoculated L. monocytogenes presented lower growth rates and shorter lag phases than the naturally-contaminated populations at all temperatures except for 5°C, where the reverse was observed. At 25°C, lag phases of the naturally- and artificially-contaminated L. monocytogenes were 11.6 and 7.8 h, respectively. The highest increase in population was observed for the artificially-inoculated pathogen at 15°C after 96 h (6.16 log CFU/mL) of storage. Growth models for both contamination states in milkshakes were determined. In addition, this study evaluated the antimicrobial effectiveness of flavoring agents, including strawberry, chocolate and mint, on the growth of the pathogen in milkshakes during 10°C storage. All flavor additions resulted in decreased growth rates of L. monocytogenes for both contamination states. The addition of chocolate and mint flavoring also resulted in significantly longer lag phases for both contamination states. This study provides insight into the differences in growth between naturally- and artificially-contaminated L. monocytogenes in a food product.